MEKANISME PEMUNGUTAN, PENYETORAN, DAN PELAPORAN PPH 22 PADA PT PESONA RAMALIYATI - Miranda, Astrid; Manurung, Jean. P.; Anggraeny, Nenny (Fakultas Ekonomi Universitas Kristen Indonesia, 2017)
Taxes are a source of goverment income that is very vital in costing country activities. Income tax is the sources of goverment income, including income tax (PPh) section 22 which is one type of goverment income. PT Pertamina (Persero) is the State-owned enterprises (SOEs) that are engaged in the sale of OIL and GAS (Oil and Gas) and PT Pesona Ramaliyati is taxpayers charged of the PPh section 22 by PT Pertamina. The purpose of this journal is to analyze whether the Voting Procedur, Tax Reporting and Remittance of income tax article 22 the company PT Pesona Ramaliyati is in compliance with the applicable Tax Regulations that is Ministerial Regulation Number 107/PMK. 010/2015 about PPh section 22. Based on the results of the data collection from PT Pesona Ramaliyati, PT Pertamina (Persero) has already done the voting procedures of the remittance and reporting of the PPh section 22 top fuel oil in accordance with the applicable Legislation, that is Regulation of the Minister of Finance Number 107/PMK. 010/2015 about PPh section 22. PT Pesona Ramaliyati is always pays income tax of article 22 in accordance with the procedures and regulations applicable at time of delivery order every day.Keyword : Tax Income Section 22, Voting Procedure, Tax Reporting and Remmitance